2016
DOI: 10.1371/journal.pone.0160561
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the ORF3 and S1 Genes of Porcine Epidemic Diarrhea Virus Non S-INDEL Strains in Seven Regions of China, 2015

Abstract: In an effort to trace the evolution of porcine epidemic diarrhea virus (PEDV), S1 and ORF3 genes of viruses identified in 41 pig farms from seven regions (North, Northeast, Northwest, Central, East, South West, and South, respectively) of China in 2015 were sequenced and analyzed. Sequence analysis revealed that the 41 ORF3 genes and 29 S1 genes identified in our study exhibited nucleotide homologies of 98.2%–100% and 96.6%–100%, respectively; these two genes exhibited low nucleotide sequence similarities with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…It is revealed that the classical PEDV exhibited weaker sugar‐binding activity than the recently uncovered G2 isolates (Deng et al., ). Amino acid substitutions were also reported in the receptor‐binding region (Wang et al., ). Whether the 8‐amino acid insertion observed in VN‐TH15/HY/2015 influences the biological functions of PEDV requires further study.…”
Section: Discussionmentioning
confidence: 85%
“…It is revealed that the classical PEDV exhibited weaker sugar‐binding activity than the recently uncovered G2 isolates (Deng et al., ). Amino acid substitutions were also reported in the receptor‐binding region (Wang et al., ). Whether the 8‐amino acid insertion observed in VN‐TH15/HY/2015 influences the biological functions of PEDV requires further study.…”
Section: Discussionmentioning
confidence: 85%
“…For amplification of the 6b gene of FCoV, RNA extraction and cDNA synthesis were carried out according to the protocol described by Wang et al. (). Random primers (six nucleotides) were used for synthesis of the first‐strand cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, RNA extraction and cDNA synthesis for the 50 samples were carried out according to the protocol described by Wang et al. () using random primers (six nucleotides) and an oligo dT18 primer. The double‐stranded DNA was synthesized by second strand cDNA synthesis kit (Beyotime Biotechnology, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Further, the novel PEDV strains with new amino acid deletions in their S genes have been found in fields in China. The S proteins of strains FJAX1 and FJAX2 were found to have a 66–67 amino acid deletion28 and the S protein of HLJ2015/DP1–1 had a 377–380 amino acid deletion29 compared with the CV777 S protein. However, the pathogenicity of these three strains has not been reported so far.…”
Section: Discussionmentioning
confidence: 98%
“…Concurrently, several variant PEDV strains, characterised by insertions and deletions (INDELs) in the S gene and designated S-INDEL PEDV, were found to be circulating in United States swine farms2425. Several strains with different deletions in the S gene were also reported in previous studies222627282930. Thus, the S gene may be important for understanding the genetic relatedness of PEDV field isolates, the epidemiological status of the virus, and for vaccine development.…”
mentioning
confidence: 90%